Understanding conference attendee's experience quality and value perception: the case of academic association conferences - Choi, Young Gin (Kansas State University, 2013)
The meeting industry has seen significant growth over the last few decades and has now become truly global. As the number of conferences increases and attendees have so many conferences to choose from, understanding how they evaluate the conference experience is more important than ever. Previous studies have focused on site selection factors, destination perception and image, economic impact, and meeting planner issues, not on the conference experience itself. Annual association conferences are lucrative because of the large number of attendees they bring to the host destination. In marketing and managing association conferences, host destinations and meeting convention organizers are increasingly interested in how attendees evaluate the conference experience. With the first conceptual model, this study sought to reveal the effect of perceived conference quality dimensions on conference experience quality dimensions. Academic association conference was taken as the context, and data were collected to validate the proposed models. A self-reported questionnaire was distributed to faculty members from twenty randomly selected universities in the United States who attended an academic association conference at least once within the past year. The hypotheses included in the conceptual model were examined based on responses from 370 faculty members in the United States. The proposed relationships were analyzed by using PLS-SEM analysis which involves evaluation of measurement model and structural model. The results indicated significant relationships among all conference specific dimensions (i.e., professional education and professional & social networking) and all conference experience quality dimensions (i.e., learning, self-esteem, and excitement). Moreover, all destination specific dimensions (i.e., site attractiveness, travelability, and site environment) had a significant relationship with excitement, but site attractiveness did not have a significant relationship with learning. With the second conceptual model, this study sought to verify the relationships among perceived conference value dimensions, satisfaction, and behavioral intentions. This study found that utilitarian value, hedonic value, and social value had significant effects on satisfaction and behavioral intentions. Given that understanding attendee behavior is critical in the meeting industry, this study benefits meeting planners and host destinations with information that allows them to maximize the conference experience for attendees, and attracting and retaining repeat attendees. The results indicated significant relationships among all conference specific dimensions (i.e., professional education and professional & social networking) and all conference experience quality dimensions (i.e., learning, self-esteem, and excitement). Moreover, all destination specific dimensions (i.e., site attractiveness, travelability, and site environment) had a significant interrelationship with excitement, but site attractiveness did not have a significant relationship with learning. With the second conceptual model, this study sought to verify the relationships among perceived conference value dimensions, satisfaction, and behavioral intentions. This study found that utilitarian value, hedonic value, and social value had significant effects on satisfaction and behavioral intentions. Given that understanding attendee behavior is critical in the meeting industry, this study benefits meeting planners and host destinations with information that allows them to maximize the conference experience for attendees, and attracting and retaining repeat attendees.
Keywords: Association conference; Perceived conference quality; Conference experience quality; Perceived conference value; Satisfaction; Behavioral intentions; Business (0310)